Xi's Military Reforms and its Efficacy in Furthering China's National Security Objectives. (September 2022) - Desai, Suyash; Kewalramani, Manoj
Chinese President Xi Jinping announced landmark military reforms in late 2015. The reforms intend to remove the 'institutional obstacles, structural contradictions and policy problems' with the aim of modernising the People's Liberation Army's (PLA) organisational structure in order to 'further unleash its combat effectiveness'. They also aim to convert the PLA into a world-class force by 2049. However, assessing the reform process in the context of organisational structures and force-specific objectives, it appears that there remains much to be desired. The reforms have certainly made the PLA a better equipped regional force. But they have, thus far, only had a limited impact in terms of preparing the PLA to meet key strategic and security objectives.